Garments and Footwear for Chronic Pain - Tajerian, Maral; Garcia, Jaqueline (Frontiers in Pain Research, 2021)
In most human societies, wearing clothing and shoes, particularly in public settings, is commonplace and may even be legally required. Consequently, there is an abundance of clothing and footwear options for individuals of different ages, genders, body shapes and catering to different needs such as workwear and active-wear. However, many of the available options may not be viable for the millions and pain sufferers worldwide, indicating a need for adaptive apparel for the pain patient. In this perspective manuscript, we focus on the availability and efficacy of clothing designed to prevent pain in the general population as well as reduce or treat pain in pain patients. Furthermore, we put forth some considerations for the construction of adaptive garments. Such efforts and needed and could significantly improve well-being and quality of life in the pain patient.